Analisis Pengaruh Audit Tenure, Struktur Corporate Governance dan Ukuran KAP Terhadap Integritas Laporan Keuangan - Nabila Ahdania Azahra; Cris Kuntadi; Fanisa eka Pratiwi (Journal of Islamic Economics and Finance, 2024)
The purpose of this research is to analyze the influence of audit tenure, corporate governance structure and KAP size on the integrity of financial reports. Develop a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) The influence of Audit Tenure on Financial Integrity; 2) Corporate Governance Structure has an influence on Financial Integrity; and 3) KAP size has an effect on financial integrity.